2009
DOI: 10.1016/j.jasms.2008.09.028
|View full text |Cite
|
Sign up to set email alerts
|

The spontaneous loss of coherence catastrophe in fourier transform ion cyclotron resonance mass spectrometry

Abstract: The spontaneous loss of coherence catastrophe (SLCC) is a frequently observed, yet poorly studied, space-charge related effect in Fourier-transform ion cyclotron resonance mass spectrometry (FTICR-MS). This manuscript presents an application of the filter diagonalization method (FDM) in the analysis of this phenomenon. The temporal frequency behavior reproduced by frequency shift analysis using the FDM shows the complex nature of the SLCC, which can be explained by a combination of factors occurring concurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 94 publications
1
38
0
Order By: Relevance
“…Aizikov et al [38] describe this phenomenon as a spontaneous loss of coherence catastrophe (SLCC). They noted that Nikolaev et al [14] also observed this phenomenon in their simulation.…”
Section: ϫ3mentioning
confidence: 99%
“…Aizikov et al [38] describe this phenomenon as a spontaneous loss of coherence catastrophe (SLCC). They noted that Nikolaev et al [14] also observed this phenomenon in their simulation.…”
Section: ϫ3mentioning
confidence: 99%
“…This is clearly evident when studying the scientific publications dedicated to this technology. There have been many papers reporting technical FTMS problems and ways to alleviate or even solve them . The limited number of direct users, but also the involved technical and mathematical complexity, were probably the reasons why most of these papers were not widely read outside of the FTMS community.…”
mentioning
confidence: 99%
“…Physical effects arising in FT-MS may also influence the measurement of isotopic abundances by an Orbitrap. These can include space charging and peak coalescence phenomena (40,41). Such effects are usually discussed in the context of mass accuracy, but they may also exert an influence on observed peak intensities when clouds of ions have near-equivalent m/z values.…”
Section: Isotopic Fidelity In Hdx-msmentioning
confidence: 99%